1996
DOI: 10.1046/j.1365-2249.1996.903599.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased mucosal synthesis of rheumatoid factor (RF) in coeliac disease

Abstract: Increased serum levels of RF have been reported in patients with gluten sensitivity. The objective of this study was to investigate the in vivo secretion of different isotypes of RF in the small bowel in coeliac disease. Nineteen patients were investigated by perfusion of a defined jejunal segment, and the jejunal perfusion fluid was analysed for the presence of IgA and IgM anti‐Fc (IgG). Five of the patients studied had serum IgA deficiency. Patients with partial/subtotal villous atrophy but no IgA deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Another study showed that unregulated immune dysfunction occurs in active celiac disease leading to enhanced mucosal RF antibody production [6]. Statistical significance was observed for active CD (p-value 0.004) as a risk factor when comparing the CD patients with and without RA serology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study showed that unregulated immune dysfunction occurs in active celiac disease leading to enhanced mucosal RF antibody production [6]. Statistical significance was observed for active CD (p-value 0.004) as a risk factor when comparing the CD patients with and without RA serology.…”
Section: Discussionmentioning
confidence: 97%
“…This RA-CD relationship is especially important because it has been postulated that immune dysfunction in RA arises from the intestinal mucosa and the increased intestinal permeability in CD leads to protein citrullination with subsequent autoantibody production in RA. Hallgren et al [6]. demonstrated that CD patients exhibit increased levels of rheumatoid factor in the gut mucosa while another study showed clinical improvement in patients with RA when kept on a gluten-free diet (GFD) [7].…”
Section: Introductionmentioning
confidence: 99%
“…37 Mucosal RF synthesis is apparently linked to the gluten response because RF in serum from patients with coeliac disease or dermatitis herpetiformis was carried only by IgA. 38 Furthermore, SIgA RF has been detected in serum from RA patients, so some intestinal RF synthesis may take place also in RA.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that IgM, which can be transported by secretory component from the mucosa into the intestinal lumen, may compensate for the lack of IgA. [5][6][7] Of the GI disorders that are present in IgA deficiency the most frequent are celiac disease, giardiasis, and nodular lymphoid hyperplasia (NLH) 8 ; however, these diseases occur more commonly in CVID. There is a 10-fold increased risk for celiac disease in patients with IgA deficiency.…”
Section: Selective Iga Deficiencymentioning
confidence: 99%